2000
DOI: 10.1021/cm9910299
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermal Behavior of Novel Si−B−C−N Ceramic Precursors

Abstract: Several boron-modified polysilazanes of general type {B[C2H4Si(R)NH]3} n (C2H4 = CHCH3 or CH2CH2) were synthesized and their thermal behavior studied. In contrast to the known derivatives with R = alkyl or aryl, we describe ceramic precursors in which the bulky moieties R are substituted with lower weight groups and/or reactive entities. Reactive units enable further cross-linking of the polymeric framework and therefore minimize depolymerization during ceramization. The polymer-to-ceramic conversion of all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(177 citation statements)
references
References 52 publications
9
167
1
Order By: Relevance
“…Fig. 18 Thermogravimetric curves of Si-B-C-N ceramic powders tested in air [10] (a), and surface morphology of the Si-B-C-N bulk ceramic oxidized at 1500 ℃ in air for 24 h (b) [67].…”
Section: Oxidation Resistance Of the Polymer-derivedmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 18 Thermogravimetric curves of Si-B-C-N ceramic powders tested in air [10] (a), and surface morphology of the Si-B-C-N bulk ceramic oxidized at 1500 ℃ in air for 24 h (b) [67].…”
Section: Oxidation Resistance Of the Polymer-derivedmentioning
confidence: 99%
“…During the pyrolyzing process, side-chain groups break; organic molecules with low molecular weight volatilize; crosslinking and curing take place in the polymer precursor. When pyrolyzing is finished, the remaining substance is an inorganic ceramic, mainly consisting of Si, B, C and N. The as-pyrolyzed ceramic generally has an amorphous structure [6], a high structural stability [7,8], a large viscosity and a nice oxidation resistance [9,10]. When the amorphous ceramic is annealed at 1800 ℃-2000 ℃ in an inert atmosphere for several hours, its structure will change into a thermodynamically stable one [8,11].…”
Section: Introduction To Si-b-c-n Ceramicmentioning
confidence: 99%
“…The occurrence of silicon most probably results from thermal decomposition of intermediate silicon nitride under evolution of nitrogen as indicated by the aforementioned abrupt weight loss at 1840 °C. The presence of free carbon in direct contact to silicon nitride can be excluded for thermodynamic reasons: Si 3 N 4 (or Si-N units in an amorphous state) would decompose at lower temperatures and would form silicon carbide [38][39][40]. Furthermore, it can be suggested that the borazine rings are connected by SiN 4 units preventing the formation of boron nitride phases at T < 1800 °C.…”
Section: Characterization Of the Si/b/n/c Ceramicmentioning
confidence: 99%
“…15,16 The advantage of singlesource precursors is the atomic-level homogeneity of their elemental compositions. In addition, a blended precursor approach to fabrication of composites can also be proposed.…”
Section: -7mentioning
confidence: 99%